2018
DOI: 10.1002/admi.201701519
|View full text |Cite
|
Sign up to set email alerts
|

Cathode and Anode Interlayers Based on Polymer Carbon Dots via Work Function Regulation for Efficient Polymer Solar Cells

Abstract: In this work, the ability of tuning work function for polymer carbon dots (PCDs) is systematically studied for the first time. Their application of both cathode and anode interlayers in polymer solar cells (PSCs) is achieved. PCDs possess abundant surface functional groups, which can be modified under control. Through regulating surface groups with more electron‐donating amino (PCD‐NH2) or electron‐withdrawing carboxy (PCD‐COOH), PCDs can decrease or increase work function of electrode, respectively. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) spectra show the presence of C—C/C=C (284.6 eV), C—N (286.0 eV), and N—H (401.1 eV) 35 bonds that may mainly correspond to the template NMD, and the additional C—N=C bonds (399.0 eV) should be related to CDs in these two composites (Figure 2e–h). UV–vis absorption and Fourier transform infrared (FTIR) spectra of the mother solutions of two composites are also similar, in which the π–π* transitions of C=C bonds (280 nm) of CDs can be obviously identified in UV–vis absorption spectra, 3638 as well as C—N and N—H bonds which can be identified in FTIR spectra (Figure S6). 3941 With the similar structure and PL properties of CDs in the mother solutions taken into account, it is presumed that the CDs embedded in both zeolite matrices are similar.…”
Section: Resultsmentioning
confidence: 84%
“…X-ray photoelectron spectroscopy (XPS) spectra show the presence of C—C/C=C (284.6 eV), C—N (286.0 eV), and N—H (401.1 eV) 35 bonds that may mainly correspond to the template NMD, and the additional C—N=C bonds (399.0 eV) should be related to CDs in these two composites (Figure 2e–h). UV–vis absorption and Fourier transform infrared (FTIR) spectra of the mother solutions of two composites are also similar, in which the π–π* transitions of C=C bonds (280 nm) of CDs can be obviously identified in UV–vis absorption spectra, 3638 as well as C—N and N—H bonds which can be identified in FTIR spectra (Figure S6). 3941 With the similar structure and PL properties of CDs in the mother solutions taken into account, it is presumed that the CDs embedded in both zeolite matrices are similar.…”
Section: Resultsmentioning
confidence: 84%
“…Control over the surface chemistry and core graphitization of carbon dots was shown to be very important also for photocatalysis and energy conversion applications , and for incorporation of CDs into optoelectronic devices. , For example, using multicomponent synthesis, it was possible to investigate the importance of nitrogen incorporation in the CD structure . Specifically, the presence of nitrogen atoms in CDs was critical for the photocatalytic hydrogen evolution from water, as a synergistic action from pyrrolic nitrogen edges as an electron transfer mediator, graphitic nitrogen as a catalytic site, and surface amines as hole traps.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed presences of abundant functional groups can regulate electron-donating or withdrawing function. Therefore, the -NH2 or -COOH functional groups containing CPDs act as cathode or anode interlayers for the development of polymer solar cells (PSCs) [70].…”
Section: Biomedical and Theranostic Applications Of Carbon Polymer Dots (Cpds)mentioning
confidence: 99%